Cybersecurity of industrial Internet of Things - Linkevych, Oksana; Bozhok, Natalia (My University, 2020)
Метою даної наукової роботи була розробка рекомендацій для впровадження і обслуговування безпечних рішень промислового Інтернету речей. Праця спирається на каркас безпеки розроблений організацією «Industrial Internet Consortium» та дає поради для реалізації на різних рівнях: обладнання, мережі та приладів. The goal of this scientific work was to work out recommendations for implementation and maintenance security Industrial Internet of Things solutions. The work is based on Industrial Internet Security Framework made by Industrial Internet Consortium and it gives advice for implementation on different levels: hardware, network, accessories.
Keywords: security; безпека; Internet of Things; networks; Інтернет Речей; мережі; кафедра ділової іноземної мови та міжнародної комунікації